Sri Lanka : Price Changes and the Poor - Gulde, Anne (IMF Working Papers; Working Paper ;, 1991)
This paper examines the short-run impact of Sri Lanka's recent structural adjustment program on the poorest segments of society. While the ultimate goal of all macroeconomic adjustment programs is to overcome structural rigidities and put the economy on a sustainable growth path, some of the measures implemented, such as the liberalization of food and energy prices, cuts in subsidies and other budgetary spending, and exchange rate changes, may cause significant increases in relative prices faced by the poor. On the other hand, there are offsetting income effects even in the short run, such as adjustments in wages and output prices and retargeting of subsidies.